FROM LIKES TO LOYALTY: THE INTERPLAY OF SOCIAL MEDIA MARKETING IN SHAPING EDUCATION INSTITUTION BRAND ATTITUDE AND LOYALTY - Sandra J.R. Kainde; Deske W. Mandagi (SEAN Institute, 2023)
This research investigates the impact of social media marketing (SMM) on brand loyalty of education institutions. With the rising utilization of social media platforms in higher education, comprehending the interconnection between social media marketing and brand loyalty has become increasingly crucial. The research employs a quantitative approach involving a sample of 250 senior high school students, utilizing Structural Equation Modelling (SEM) technique in SmartPLS software to analyze the collected data. The study aims to examine the influence of SMM activities on students' attitude towards educational institutions brand and their loyalty. The findings reveal that SMM plays a vital role in shaping students' attitudes towards educational institutions and in building their loyalty towards those institutions. Furthermore, the influence of SMM on brand loyalty is mediates by brand attitude. The study concludes with practical implications for educational marketers to effectively utilize social media marketing strategies to establish brand loyalty and enhance the overall reputation of their institution